2008
DOI: 10.1177/0275074007309151
|View full text |Cite
|
Sign up to set email alerts
|

Nonprofit Board Role Ambiguity

Abstract: This study investigates the degree to which nonprofit board volunteers understand their role and performance expectations in the organizations they govern. Using data collected from chief executives and board members, the authors first compare board member self-reports of role ambiguity with chief executive assessments of how well board members understand their roles. They then examine the antecedents and consequences of board role ambiguity, finding that training and feedback can decrease role ambiguity and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…This finding is consistent with what Wright and Millesen (2008) and Widmer (1993) refer to as board role ambiguity. As Wright and Millesen (2008) define board role ambiguity as a situation wherein "when board members do not know or understand the performance expectations and established standards of behavior" (p 333). They argue that this lack of understanding of the role of the board has a negative impact on board performance and that training and hands-on coaching can decrease role ambiguity among board members.…”
Section: Discussionsupporting
confidence: 89%
“…This finding is consistent with what Wright and Millesen (2008) and Widmer (1993) refer to as board role ambiguity. As Wright and Millesen (2008) define board role ambiguity as a situation wherein "when board members do not know or understand the performance expectations and established standards of behavior" (p 333). They argue that this lack of understanding of the role of the board has a negative impact on board performance and that training and hands-on coaching can decrease role ambiguity among board members.…”
Section: Discussionsupporting
confidence: 89%
“…This study also explores the role of training. Although training is touted as an important mechanism to improve board performance, there is relatively modest research exploring impact on directors' behavior (Wright & Millesen, 2008). As depicted in Figure 1, the current study examines the relationships between board capital, three factors (training, sense of community, and mission attachment), and board member engagement in two areas (monitoring and resource).…”
mentioning
confidence: 99%
“…Similarly, Wright and Millesen (2008) found that board role ambiguity was related to a disconnect between what board members believed their roles to be and what chief executives expected. We suspect that, for many board members, the self-assessment process might be the first time they were introduced to the full range of board roles and responsibilities; thus, a certain amount of confusion, ambiguity, and uncertainty is expected.…”
Section: Resultsmentioning
confidence: 98%